Caracterização da carne de Tilápia do Nilo (Oreochromis niloticus) submetida à dietas suplementadas com óleo de peixe - Duarte, Francine Oliveira Souza (2017)
Nile tilapia (Oreochromis niloticus) is one of the most commercially cultivated species in the world, being preferred for its high rusticity and adaptability, fast growth and meat with desirable characteristics, such as low in fat, absence of "Y" spines and firm texture, much appreciated by consumers, which generates good acceptance in the market. To boost animal production, nutritional aids are sought for the animal diet in order to maintain fish health, obtain better rates of zootechnical performance and satisfactory meat quality. Fish oil, a by-product of the fishing industry, has been used as a supplement in animal feed and is recognized for its positive effects also on human health, since it is rich in polyunsaturated fatty acids of the family omega 3, effectively acting in the reduction of incidence of cardiovascular diseases, rheumatic disorders of the nervous system, promoting the strengthening of the immune system. Thus, it is through dietary supplementation of Nile tilapia with fish oil that a greater increase of fatty acids essential to their meat is sought in order to add value to the product and reaffirm it as a functional nutraceutical food, able to provide benefits to the human health, especially by preventing and reducing risks of disease. For this, different levels of inclusion of fish oil in the tilapia ration (5%, 10% and 15%) were tested for periods of 30 and 60 days pre-slaughter. At the end of the experiment, the economic evaluation was carried out, as well as the verification of the blood biochemistry and the indices of productive performance. After the fish were slaughtered and filleted, the steaks were properly packed and stored in freezing temperatures at -40°C for the subsequent physical-chemical analysis of the meat, covering the profile of fatty acids, centesimal composition, mineral elements content, cholesterol, vitamin E, lipid oxidation, color, pH, and texture-related characteristics such as weight loss by thawing, weight loss by cooking, water retention capacity, total and soluble collagen content, and myofibrillar fragmentation index. The treatments with fish oil were significant (P<0.05) only as regards the meat mineral content and the nutritional quality of the fillet lipid profile. For the other attributes, there were positive tendencies to meat quality, since it presented low fat and cholesterol content, a satisfactory centesimal composition for the species, efficient oxidative stability and a lighter fillet coloration with yellowish tones compatible with the taste of the consumer. Regarding the firmness of the fish meat, no influences of the supplemented feed on the analyzes were verified. However, texture improvement was noted due to the increase in CRA, which makes the product more succulent, and greater shear force in products submitted to the cooking process.